The social effects of the deterioration of security in 2014, the exacerbation of the problem of orphans in the urban areas of Al-Muthanna Governorate as a model (Journal of the College of Basic Education, 2022)
The research showed the existence of a relationship between the security deterioration that the country witnessed in 2014 and the invasion of ISIS terrorist gangs in some Iraqi cities and the accompanying military operations, an increase in the number of orphans in the urban areas of Al-Muthanna Governorate. Between the year 2020, which gave a clear picture of the increase in the number of orphans in the governorate’s urban areas as a result of these operations